The Honor Paradox: Rethinking Academic Distinction and Mathematical Ability in Senior High School Graduates - Temones, John Ben; Dacoro, Jaslyn; Gamelo, Haizel; Hallare, John Kevin; Villaralvo, John Paul; Violanda, Bea (LPPI Yayasan Almahmudi bin Dahlan, 2025)
Despite being awarded academic honors, many Filipino students continue to underperform in mathematics—a disconnect highlighted by recent PISA results. This mixed-method case study interrogates the credibility of honor-based distinctions as indicators of actual mathematical competence. Focusing on 40 first-year mathematics education students at a state university, the study correlated senior high school honors with mathematics diagnostic test performance and investigated underlying factors through a validated survey. Of the 40 participants, 37 held academic honors, yet only 2 passed the test. Fisher’s Exact Test (α = 0.05) revealed no statistically significant relationship between honors and performance. Exploratory factor analysis uncovered three latent dimensions contributing to this discrepancy: (1) educational value and personal growth, (2) mathematical engagement and self-efficacy, and (3) resource availability and teacher support. These findings challenge the assumption that academic honors are reliable proxies for competence. They call into question the meritocratic logic underpinning institutional reward systems, urging a critical reassessment of how educational success is defined, measured, and recognized.